Approaches to osteoarthritis - A qualitative study among patients in a rural setting in Central Western India. (2nd November 2022) - Swärdh, Emma; Jethliya, Gitanjali; Khatri, Subhash; Kindblom, Kristina; Opava, Christina H
ABSTRACT: Background: Osteoarthritis (OA) represents a major cause of disability in India. For implementation of best practice management, it is important to consider the views of people in India since they might deviate from those expressed in previous studies by people with OA in the Western world. Objective: The purpose of this study was to explore and describe approaches toward OA and its management among patients in a rural setting in Central Western India. Design and Method: Conventional content analysis was used to analyze semi-structured interviews with 24 patients diagnosed with OA from the target area of Pravara University Hospital and ten adjacent primary health care centers in Maharashtra, India. Results: Four categories; lack of power, active ambivalence, taking control and a constant struggle were identified as patients' approaches to OA. The categories were further elaborated on in seven subcategories. Conclusion: Daily challenges and efforts, of which some may be unique to patients in a rural setting in India, underlie passive and active approaches to OA and its management. Understanding these may enhance Indian physiotherapists' implementation of evidence-based self-management programs adapted to Indian conditions and reduce the distress of their patients.